Gallic acid mitigates diclofenac-induced liver toxicity by modulating oxidative stress and suppressing IL-1β gene expression in male rats. (1st January 2020) - Esmaeilzadeh, Mohsen; Heidarian, Esfandiar; Shaghaghi, Mehrnoosh; Roshanmehr, Hoshang; Najafi, Mohammad; Moradi, Alireza; Nouri, Ali
Abstract: Context: Diclofenac (DIC) is an NSAID and consumption of this drug creates side effects such as liver injury. Gallic acid (GA), a natural component of many plants, is used as an antioxidant agent. Objective: This study assesses the hepatoprotective effects of GA in the rat model of DIC-induced liver toxicity. Materials and methods: In this research, the male Wistar rats were separated into five groups ( n  = 6). Group 1, control, received normal saline (1 mL/kg bw, i.p.); Group 2 received DIC-only (50 mg/kg bw, i.p.); Groups 3, received DIC (50 mg/kg bw, i.p.) plus silymarin (100 mg/kg bw, po), groups 4 and 5 received DIC (50 mg/kg bw, i.p.) plus GA (50 and 100 mg/kg, po, respectively). Results: The data demonstrated that the liver levels of the GSH, GPx, SOD, and CAT significantly reduced and the levels of the serum protein carbonyl, AST, ALP, ALT, total bilirubin, MDA, serum IL-1β, and the liver IL-1β gene expression were remarkably increased in the second group compared to control group. On the other hand, treatment with GA led to a significant elevation in GSH, GPx, SOD, CAT, and a significant decrease in protein carbonyl, AST, ALP, ALT, total bilirubin, MDA, serum IL-1β, and gene expression of IL-1β in comparison with the second group. Histological changes were also ameliorated by GA oral administration. Discussion and Conclusions: The data show that the oral administration of GA could alleviate the noxious effects of DIC on the antioxidant defense system and liver tissue.